Avaliações econômicas em saúde: apuração de custos no atendimento de gestações complicadas pelo diabete - Cavassini, Ana Cláudia Molina; Lima, Silvana Andréa Molina [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (My University, 2010)
Cost evaluation is an important work tool in hospital management optimization as it shows managers the results that are in accordance with expected parameters and those that require correction. It also helps the determination of sale prices, investment decisions, the expansion of hospital facilities and the definition of stock volumes of material and medicines. Costs can be classified as direct, indirect, variable and fixed, and they can be estimated by different costing systems, such as absorption costing and activity-based costing (ABC). From this information, various economic evaluations are performed: disease cost and comparison of disease cost, costminimization, cost-usefulness, cost-effectiveness and cost-benefit. Considering the importance of cost control in health care institutions and the teaching of cost estimation in health care, basic concepts, cost types, costing systems and economic evaluation types were presented in this study. Finally, cost worksheets were proposed for the use in outpatient units and hospitals for the treatment of pregnancies complicated by diabetes.

A avaliação de custos é importante instrumento de trabalho na otimização do gerenciamento hospitalar, indicando ao administrador os resultados que estão dentro dos parâmetros esperados e aqueles que exigem correção. Tal avaliação auxilia também na determinação do preço de venda, nas decisões de investimentos, na expansão de instalações hospitalares e na definição de volumes de estoques de materiais e medicamentos. Os custos podem ser classificados em diretos, indiretos, variáveis e fixos, e podem ser calculados por diferentes sistemas de custeio; entre eles, cálculo por absorção, procedimento ou atividade ABC. A partir desses dados, diversas avaliações econômicas são realizadas: custo e comparação do custo da doença, custo-minimização, custo-utilidade, custo-efetividade e custo-benefício. Tendo em vista a importância do controle de custos nas instituições de Saúde e do ensino do cálculo de custo nessa área, foram apresentados neste estudo os conceitos básicos, os tipos de custos, os sistemas de custeio e os tipos de avaliações econômicas. Finalmente, foram propostas planilhas de custo para uso em atendimento ambulatorial/hospitalar de gestações complicadas por diabete.
Economic evaluations in health care: counting the costs in the care of pregnancies complicated by diabetes
Keywords: Health care costs; Diabetic pregnant women; Cost management; Health care financial administration; Custos em saúde; Gestantes diabéticas; Gerenciamento de custos; Administração financeira em saúde